ANALYSIS OF THE INTEGRATION OF ISLAMIC VALUES IN THE PROCESS OF DIGITIZING LEARNING FOR STUDENTS OF ISLAMIC UNIVERSITY 45 BEKASI - Abiyu Rifky Yandi Harahap; Baruna Jaya Hartanto (DAS Institute, 2026)
Digitalization of learning has become a phenomenon that penetrates almost all lines of education. Along with technological developments, the application of Islamic values in education needs to be evaluated so that digital learning remains relevant to Islamic principles. This study aims to analyze the extent to which Islamic values can be integrated in the learning digitization process at Patrima Islam University Bekasi. Using a mixed method consisting of student surveys, interviews with lecturers, and document analysis, this research reveals the challenges and opportunities in integrating Islamic values in technology-based learning. The results are expected to provide recommendations for the development of digital learning that is more effective and in accordance with Islamic principles.